1997
DOI: 10.21273/hortsci.32.3.476a
|View full text |Cite
|
Sign up to set email alerts
|

Development and Abortion of Flowers in Capsicum annuum Exposed to High Temperatures

Abstract: Reduction of floral number in Capsicum annuum has been observed during growth at high temperature. To determine whether decreased flower production or increased flower abscission is a direct response to high temperatures or a response to water stress induced by high temperatures, we compared flowers and fruit produced and flowers aborted to leaf growth rate, osmotic potential, stomatal conductance, and chlorophyll fluorescence of two cultivars. To determine the stage(s) of fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…They reported that, as the mean daily temperature increase the number of fruits per plant also increased. Erickson and Markhart (1997) noted that, temperature is the primarily factor in the decrease of fruit production as reduced fruit set was due to flower abortion and not due to decreased flower Awole et al 12665 initiation or plant growth. Cocharn (1964) showed that, the poor fruit set at high temperature to be due to excessive transpiration by the plant which could partly be the cause for the differences observed in this study.…”
Section: Yield and Yield Componentsmentioning
confidence: 99%
“…They reported that, as the mean daily temperature increase the number of fruits per plant also increased. Erickson and Markhart (1997) noted that, temperature is the primarily factor in the decrease of fruit production as reduced fruit set was due to flower abortion and not due to decreased flower Awole et al 12665 initiation or plant growth. Cocharn (1964) showed that, the poor fruit set at high temperature to be due to excessive transpiration by the plant which could partly be the cause for the differences observed in this study.…”
Section: Yield and Yield Componentsmentioning
confidence: 99%